1.9k views
5 votes
Use the Quadratic Formula to solve the equation. -2x^2 - 5x + 5 = 0

2 Answers

6 votes
The answer is going to be in the picture because trying to make fractions with this is too difficult. :D

Use the Quadratic Formula to solve the equation. -2x^2 - 5x + 5 = 0-example-1
User Chris Schmich
by
5.1k points
1 vote

Answer:


x = (5 \pm √( 65 ))/(-4).

Explanation:

The Quadratic Formula for a second degree polynomial
ax^(2) +bx+c=0 is a formula for the values of its solution i.e. for finding the values of x.

It is given by,
x = \frac{-b \pm\sqrt{b^(2)-4ac }}{2a}.

Now, we have the given quadratic equation
-2x^(2)-5x+5 = 0,

which gives a = -2 , b = -5 , c = 5.

Substituting the value of a, b , c in the above formula, we get


x = \frac{-(-5) \pm \sqrt{(-5)^(2) -4 * (-2) * 5 }}{2 * (-2)}.


x = (-(-5) \pm √( 25 + 40 ))/(-4).


x = (5 \pm √( 65 ))/(-4).

Hence, the solution of the given quadratic equation is
x = (5 \pm √( 65 ))/(-4).